2015
DOI: 10.1016/j.chembiol.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking the E3 Ubiquitin Ligase Cereblon to Efficiently Target BRD4

Abstract: Summary BRD4, a bromodomain and extraterminal domain (BET) family member, is an attractive target in multiple pathological settings, particularly cancer. While BRD4 inhibitors have shown some promise in MYC-driven malignancies such as Burkitt’s Lymphoma (BL), we show that BRD4 inhibitors lead to robust BRD4 protein accumulation, which may account for their limited suppression of MYC expression, modest anti-proliferative activity and lack of apoptotic induction. To address these limitations, we designed ARV-825… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
865
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 908 publications
(929 citation statements)
references
References 37 publications
19
865
0
5
Order By: Relevance
“…In our prior research, we directed the degradation of BET family proteins by appending CRBN ligands to JQ1, resulting in rapid and potent degradation of BRD2, BRD3 and BRD4. These findings have been well validated, suggesting a broader utility of this strategy [20][21][22] .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In our prior research, we directed the degradation of BET family proteins by appending CRBN ligands to JQ1, resulting in rapid and potent degradation of BRD2, BRD3 and BRD4. These findings have been well validated, suggesting a broader utility of this strategy [20][21][22] .…”
Section: Introductionmentioning
confidence: 75%
“…In our prior research, we directed the degradation of BET family proteins by appending CRBN ligands to JQ1, resulting in rapid and potent degradation of BRD2, BRD3 and BRD4. These findings have been well validated, suggesting a broader utility of this strategy [20][21][22] .Toward the elaboration of BRD9-directed degraders, we initially evaluated putative pharmacophores from reported bromodomain probes LP99 and I-BRD9, and subsequently expanded our study to a third probe, BI7273, reported during the course of this research (Figure 1 A). [12,14,15] To explore the potential of bifunctional derivatives to induce BRD9 degradation, we initially selected as our starting point a close chemical analog of I-BRD9 described by GlaxoSmithKline (GSK-39).…”
mentioning
confidence: 99%
“…dBET1 and ARV-825 consist of BET inhibitors, (+)-JQ1 and OTX-015, respectively, coupled via a spacer moiety to a ligand of E3 ubiquitin ligase. [52][53][54][55] dBET1 induced selective CUL4-RBX1-DDB1-cereblon (CRBN)-dependent degradation of BET family proteins, including BRD2, BRD3 and BRD4, in vitro and in vivo, and it delayed leukemia progression in mice. 54) ARV-825 induced BRD4 degradation via a CRBN-mediated and proteasome-dependent mechanism, leading to persistent suppression of c-MYC and its downstream signaling.…”
Section: Inducers Of Bet Degradationmentioning
confidence: 99%
“…54) ARV-825 induced BRD4 degradation via a CRBN-mediated and proteasome-dependent mechanism, leading to persistent suppression of c-MYC and its downstream signaling. 55) ARV-825 inhibited cell proliferation and induced apoptosis in Burkitt's lymphoma (BL), which is MYC-driven malignancy. 55) Both dBET1 and ARV-825 were more effective against cancer cells than JQ1 or OTX-015 alone.…”
Section: Inducers Of Bet Degradationmentioning
confidence: 99%
See 1 more Smart Citation